صيغ الفعل الثلاثي المجرد وتوظيفها في الصرف التعليمي: دراسة في ضوء نظريَّة المخالفة والموافقة = The moods of un-augmented trilateral verbs and their use in applied morphology: a study in the light of the assimilation and dissimilation theory = Bentuk-bentuk Kata kerja “Fi'il al-Thulathi al-Mujarrad” dan penggunaannya dalam morfologi gunaan: satu kajian berdasarkan teori asimilasi dan disimilasi - Dollah, Nafi@Hanafi; Abdullah, Nur Azlina (International Islamic University Press, 2014)
أﺛﺒﺖ اﻹﺣﺼﺎء اﻟﺬي أﺟﺮاﻩ اﻟﺒﺤﺚ أّن اﻷﻓﻌﺎل اﻟ ﺮدة اﻟﻮاردة ﰲ اﳌﻌ ﺜﻼﺛﻴﺔ ا ﺎﺟﻢ اﻟﻌﺮﺑﻴﺔ اﻟﱰاﺛﻴﺔاﻟﺸﺎﻣﻠ ا، ﻓﻘﺪ ﺑﻠﻎ ﻋﺪدﻫﺎ ﰲ ﻣﺜﻼً - ﺣﻮاﱄ ﺳﺘﺔ آﻻف – " ﺔ ﻛﺜﲑة ﺟﺪ"ﻟﺴﺎن اﻟﻌﺮب (ﻓﻌﻼً، ﺑﻴﻨﻤﺎ ﻳﺒﻠﻎﻋﺪدﻫﺎ ﰲ أﻛﱪ اﳌﻌﺎﺟﻢ اﻟﺸﺎﻣﻠﺔاﳊﺪﻳﺜﺔ 6662)وﺳﺘﻤﺌﺔ واﺛﻨﲔ وﺳﺘﲔ (ﻓﻌﻼ . وﻟﻘﺪ أدرك ﻋﻠﻤﺎء اﻟﻠﻐﺔ اﻟﻌﺮﺑﻴﺔ 6272) ﺣﻮاﱄ ﺳﺘﺔ آﻻف وﻣﺌﺘﲔ واﺛﻨﲔ وﺳﺒﻌﲔ اﳌﻌﺎﺻﺮون اﻟﺒﺎﺣﺜﻮن وﻛﺬﻟﻚ اﳌﺪﱢرﺳﻮن اﳌﻤﺎرﺳﻮن ﻟﻠﺘﻌﻠﻴﻢ ﺻﻌﻮﺑﺔ ﺑﺎﻟﻐﺔ ﻳﻮاﺟﻬﻬﺎ ﻣﺘﻌﻠﻤﻮن اﻟﻠﻐﺔ اﻟﻌﺮﺑﻴﺔ ّﺮدة وﺗﻄﺒﻴﻖ ﻗﻮاﻋﺪﻫﺎ ﻟ ﰲ ﺿﺒﻂ ﺻﻴﻎ اﻷﻓﻌﺎل اﻟﺜﻼﺛﻴﺔ ا ﻜﺜﺮة وﺟﻮد اﻟﺸﻮاذ ﻋﻦ ﺗﻠﻚ اﻟﻘﻮاﻋﺪ .ﻓﻤﺎ زاﻟﺖ ﻣﺴﺄﻟﺔ اﻟﺘﻌﺎﻣﻞ ﺑﺼﻴﻎ اﻷﻓﻌﺎل اﻟﺜﻼ ﺮدة، و ﺛﻴﺔ ا ﺿﺒﻂ ﺣﺮﻛﺎت ﻋﻴﻨﻬﺎ ﲤﺜﱢﻞ واﺣﺪة ﻣﻦ أﻫّﻢ اﳌﺸﻜﻼت اﻟﺼﺮﻓﻴﺔ اﻟﻌﺮﺑﻴﺔ ﺑﺴﺒﺐ ﺗﻠﻚ اﻟﻜﺜﺮة ﰲ ﰲ اﻷﻓﻌﺎل اﻟﺜﻼﺛﻴﺔ اﳉﺮدة، واﻟﺘﻨﱡﻮع ﰲ اﻟﺼﻴﻎ، واﻟﺸﺬوذ ﻋﻦاﻟﻘﻮاﻋﺪ .وﻗﺪﳝًﺎ ﺣﺎول اﺑﻦ ﺟﲏ ﺗﻔﺴﲑ ﻫﺬﻩ اﻟﻈﺎﻫﺮة وﺿﺒﻄﻬﺎ ﻣﻦ ﺧﻼل ﻧﻈﺮﻳﺔاﳌﺨﺎﻟﻔﺔواﳌﻮاﻓﻘﺔ .وﻗﺪ أﺧﺬﻋﻠﻤﺎءاﻟﻌﺮﺑﻴﺔ اﶈﺪﺛﻮن ﺬﻩ اﻟﻨﻈﺮﻳﺔ *أﺳﺘﺎذ ﻣﺸﺎ ركﺑﻘﺴﻢ ﺎ، ﺑ اﻟﻠﻐﺔ اﻟﻌﺮﺑﻴﺔ وآدا ﻜﻠﻴﺔ ﻣﻌﺎرف اﻟﻮﺣﻲ واﻟﻌﻠﻮم اﻹﻧﺴﺎﻧﻴﺔ ﺑﺎﳉﺎﻣﻌﺔ اﻹﺳﻼﻣﻴﺔ اﻟﻌﺎﳌﻴﺔ ﲟﺎﻟﻴﺰﻳﺎ، hanafi@iium.edu.my: اﻟﱪﻳﺪ اﻹﻟﻜﺘﻮرﱐ **اﶈﺎﺿﺮة ﲟ ﺮ ﻛﺰ اﻟﻠﻐﺎت، ﳉﺎﻣﻌﺔ اﻹﺳﻼﻣﻴﺔ اﻟﻌﺎﳌﻴﺔ ﲟﺎﻟﻴﺰﻳﺎ. ﻋﺸﺮ 44 اﻟﺘﺠﺪﻳﺪـــاﳌﺠﻠﺪاﻟﺜﺎﻣﻦ .واﻟﺜﻼﺛﻮن 143 . اﻟﻌﺪداﻟﺴﺎدس 201 /ھ 6 م 4 أﻳًﻀﺎ، إﻻ أ ﻢ ﱂ ﻳﻬﺘﻤﻮا ﺑﺎﳉﺎﻧﺐ اﻹﺣﺼﺎﺋﻲ ﻹﺛﺒﺎت اﻟﻈﺎﻫﺮةﳏﻞ اﻟﻨﻈﺮ أوﺗﻔﻨﻴﺪﻫﺎ . وﻟﺬﻟﻚ ﻳﺘﻨﺎول اﻟﺒﺤﺚ اﳊﺎﱄ ﺑﺼﻮرة إﺣﺼﺎﺋﻴﺔ ﻫﺬﻩ اﻟﻈﺎﻫﺮة ﻛﻤﺎ ﲡﻠﺖ ﰲ اﳌﻌﺠﻢ اﻟﻌﺮﰊ اﻟﱰاﺛﻲ اﻟﺸﺎﻣﻞﻟﻴﺤﺼﻲ ﻣﺎ ﻳﻮاﻓﻖ ﺗﻠﻚ اﻟﻘﻮاﻋﺪ وﻣﺎ ﳜﺎﻟﻔﻬﺎ ﺳﻌﻴًﺎ ﻹﺛﺒﺎتﻟﻨﻈﺮﻳﺔ اﳌﺨﺎﻟﻔﺔ واﳌﻮاﻓﻘﺔ ﺣﺴﺐ اﳌﻌﻄﻴﺎت اﻹﺣﺼﺎﺋﻴﺔ اﻟﺪﻗﻴﻘﺔ. واﻟﻘﺼﺪ ﻣﻦ ذﻟﻚ ﺎ ﰲ اﻻﺳﺘﻔﺎدة ﺗﺪرﻳﺲ اﻟﺼﺮف، وإﻋﺪاد اﻟﻜﺘﺐ اﻟﺘﻌﻠﻴﻤﻴﺔ، وﻣﺴﺎﻋﺪة اﳌﺘﻌﻠﻤﲔ ﻋﻠﻰ ﻣﻌﺮﻓﺔ اﻷوزان اﻟﺼﺮﻓﻴﺔ ﻟﺘﻠﻚ اﻷﻓﻌﺎل اﻟﻌﺮﺑﻴﺔ، وﺗﺴﻬﻴﻞ ﻃﺮق اﻛﺘﺸﺎﻓﻬﺎ ﺗﻠﻚ ﻷﻓﻌﺎل ﰲ ﺑﻌﺾ اﳌﻌﺎﺟﻢ. اﻟﺼﻴﻎ اﻟﺼﺮﻓﻴﺔ ﺮد ، اﻟﻜﻠﻤﺎت اﻷﺳﺎﺳﻴﺔ:اﻟﻠﻐﺔ اﻟﻌﺮﺑﻴﺔ، اﻟﺼﺮف اﻟﻌﺮﰊ ، ، اﻟﺜﻼﺛﻲ ا ﻧﻈﺮﻳﺔ اﳌﺨﺎﻟﻔﺔ واﳌﻮاﻓﻘﺔ. Abstract The statistical survey carried out by the researchers has shown that unaugmented trilateral verbs occurring in comprehensive classical Arabic lexicons are so numerous. In the famous LisÉn al-ÑArab, they amount to about 6662 verbs, whereas their number in the largest modern dictionary is, roughly speaking, 6272 verbs. It has been realized by modern scholars as well as teachers of Arabic that learners of the Arabic language are faced with a great difficulty in grasping the moods of un-augmented trilateral verbs and applying the many rules governing them due to the existence of a large number of exceptions to those rules. Thus making use of the moods of the un-augmented trilateral verb and the vowelizing of its second radical remains one of the greatest problems in Arabic morphology as a result of that multitude of moods, rules, and exceptions. In the past, Ibn JinnÊ made an attempt to explain this phenomenon and bring it under control by developing the dissimilation theory, which has been embraced by modern scholars of Arabic too. However, these scholars did not concern themselves with the statistical confirmation or negation of this phenomenon. Therefore, the present study examines statistically the phenomenon in question as manifested in classical Arabic lexicons in a balanced manner in order to identify what conforms to the rules and what deviates therefrom in an attempt to prove the assimilation and dissimilation theory based on precise statistical data. The aim of this attempt is to apply this theory in the teaching of Arabic morphology, designing textbooks and assisting learners of Arabic in knowing the moods of those verbs and making it easier for them to arrive at such verbs in some Arabic lexicons. Key words: Arabic language, Arabic morphology, morphological moods, un-augmented trilateral verbs, assimilation and dissimilation theory